Membrane za in vitro testiranje dermalne absorpcije - Gosenca Matjaž, Mirjam (Farmacevtski vestnik, 2009)
The assessment of dermal absorption of molecules is one of the main steps in the initial design and later in the evaluation of dermal or transdermal drug delivery systems. Laboratory test systems require a membrane to mimic the barrier function of stratum corneum. The following membranes are discussed: synthetic membranes, animal models, human skin and reconstructed human epidermis.
Keywords: absorpcija; dermatologija; drug; koža; membrane; zdravila